Flexion location of the first metatarsophalangeal joint and the location of forefoot bend in general purpose women's footwear. Issue 3 (June 2019) - Thompson, Anette T.; Zipfel, Bernhard; Muzigaba, Moise; Aldous, Colleen M.
Highlights: By three dimensional laser scanning, the flexion location of the first metatarsophalangeal joint was compared to the flexion location in general purpose women's footwear. The location of the first MP joint differs substantially from British (used in South Africa) and North American last design parameters. The range of different first metatarsophalangeal joint fulcrum locations form a wide proximo-distal band described as the flexion zone. Ethnic population groups, weight, tread width and forefoot girth variables were significantly associated with the position of the first metatarsophalangeal joint. Presents the potential of ill-fitting footwear to cause harm and prevent healing after surgery. Abstract: Background: General purpose footwear could have a built-in flexion location which may not match the anatomical fulcrum location for an individual's foot. Mismatched fulcra impact on joint function, and may delay healing of an injured first metatarsophalangeal joint (first MP joint). This study compared the location of the first MP joint in an asymptomatic sample of the South African female population to the bend location set within the lasts (used by footwear manufacturers) to find whether mismatches of the flexion locations of the joint to the bending location of the footwear were likely. Methods: The study used a three dimensional foot measurement database of 453 female participants to find the fulcrum location of the first MP joint. The distance between the heel and the first MP joint was expressed as a percentage of the overall length of the unshod foot. Similar measures for sandals and closed shoes were derived, and all were compared to manufacturer last data. Results: The location of first MP joint ranged from 70% to 79% of total foot length, significantly different from last design specifications of 63% or 66% (p < 0.0001). The range of first MP joint fulcrum locations in the same size feet occurred in a wide 24 mm mediolateral band under the forefoot, termed a flexion zone. Conclusions: The first MP joint cannot properly function as a fulcrum unless footwear has a matching flexion location. Footwear designs should incorporate a wide flexion zone located under the forefoot to permit the range of first MP joint flexion locations. Recommendations to patients are to select appropriate flexible footwear to prevent shear forces, reduce strain, prevent injury and enable range of motion function and healing of injury.